Situated Narratives and Sacred Dance : Performing the Entangled Histories of Cuba and West Africa - Flanders Crosby, Jill; Torres, J. T. (Book collections on Project MUSE., 2021)
"Through a revolutionary ethnographic approach that foregrounds storytelling and performance, this book explores shared ritual traditions between the Anlo-Ewe people of West Africa and their descendants, the Arará of Cuba, who were brought to the island in the Atlantic slave trade"--